Superior anti-icing strategy by combined sustainable liquid repellence and electro/photo-responsive thermogenesis of oil/MWNT composite. (15th July 2020) - Kim, Aeree; Kim, Seonghyeon; Huh, Myoung; Kim, Hyungmo; Lee, Chan
Abstract: This paper introduces an effective anti-icing strategy that uses passive anti-icing property and active de-icing functions concurrently. These dual capabilities can alleviate the icing problem more effectively than either a passive or active function alone. The developed material is a slippery liquid-repellent elastic conductor (SLEC); it is an organogel that is composed of multi-walled carbon nanotubes, oil, and polydimethylsiloxane. The SLEC maintains passive water-droplet sliding ability even on wet surfaces that frequently occur in cold conditions (e.g., during condensation and defrosting), suppresses ice nucleation, and shows ice adhesion strength as low as ∼ 20 kPa. The SLEC releases heat when it is subject to electrical or photonic stimulation, and can therefore it can prevent ice formation and melt ice that has already formed on a surface. This material has sustainable liquid repellence by syneresis and replenishment; this ability ensures long-lasting anti-icing property, and results in exceptional durability. This durability is stable against mechanical damage. The superior dual anti-icing capabilities together with the sustainable and stable liquid repellence should generate synergistic effects, and yield a powerful anti-icing tool that can broaden the range of icing applications.